Exclusionary School Discipline Policies and Mental Health in a National Sample of Adolescents without Histories of Suspension or Expulsion. Issue 1 (January 2022) - Eyllon, Mara; Salhi, Carmel; Griffith, John L.; Lincoln, Alisa K.
We apply the theory of collateral consequences and a social stress process framework to school discipline to examine whether exclusionary school discipline policies are associated with the mental health and wellbeing of adolescents who have never been suspended or expelled and whether this association varies across race/ethnicity. Data are from 8, 878 adolescents in the National Longitudinal Study of Adolescent to Adult Health. Hierarchical linear models examined associations between discipline policies and adolescent depressive symptoms and school-connectedness, and modification by race/ethnicity. Schools had high levels of exclusionary discipline for both violent and non-violent infractions. More exclusionary policies were associated with higher levels of depressive symptoms ( b  = 1.03, 95% CI: 0.15, 1.91, p  < .05). Sense of school-connectedness was not associated with disciplinary policies. Neither association was modified by race/ethnicity.